Graduate Students’ Perceptions and Attitudes of Peer Assessment on Academic Writing - Thoip Nasution, Putra; Putri, Hidayana (AMI: JURNAL PENDIDIKAN DAN RISET, 2025)
The main objectives of this research are analyzed about the perceptions of graduate students in peer assessment of academic writing, the graduate students’ attitudes towards peer assessment, also challenges and benefits on graduate students’ writing in their practice of peer assessment. Thirty graduate students from different disciplines of Faculty of Educational Sciences at Syarif Hidayatullah State Islamic University were enrolled to participate in this research. The current study adheres to the qualitative method, and its data collected via two questionnaires of perception and attitude toward peer assessment, and semi-structured interviews with the tenth graduate students selected voluntarily. Findings showed that the graduate students’ perception and attitude towards peer assessment is slightly positive. In addition, the benefits of peer assessment are increased learning, transferable skills, authentic assessment, feedback skills, understanding standards, and peer assessment provided learning from others and team-group while the challenges of peer assessment are lacked time and cost needed, graduate students’ motivation, and feedback skills.